"Tailoring homely meals": Family members' motivations underlying nursing home visits during residents' meals. Issue 4 (29th April 2020) - Tsai, Meng‐Rung; Tsai, Hsiu‐Hsin; Tsai, Yun‐Fang; Liao, Fang‐Yu
Abstract: Aim: Elderly nursing home residents are often malnourished or at risk of malnutrition. Family members often visit residents during mealtimes, which might be an ideal opportunity for interventions targeted at improving the nutritional status of older residents. Therefore, this study aimed to explore motivations behind family member visits with nursing home residents during mealtime in Taiwan. Methods: This phenomenological study was conducted with family members of residents from four nursing homes in Taiwan. Participants were purposively sampled. Data were collected with individual face‐to‐face interviews from 18 family members. Data from transcribed audio‐recorded interviews were analyzed using the approach of van Manen. Results: Analysis of the interview data identified the essence of motivations underlying family members' visits to nursing home residents during mealtimes, which we termed "tailoring homely meals." This referred to providing food tailored to residents' needs, providing a comforting family atmosphere, assisting residents during mealtime, and monitoring food consumption. Conclusions: The motivations of family members to visit during mealtime could guide healthcare professionals working with East Asian populations in developing interventions to reduce the possibility of malnutrition, while also improving their quality of life. We recommend providing the following for nursing home residents: a nutritious and balanced diet, supporting their independence and ability to feed themselves, and encouraging involvement of family members during mealtimes.